Impacts of the changing climate on agricultural productivity and food security: Evidence from Ethiopia - Mohammad Abedin (Journal of Cleaner Production, 2024)
This study investigates the influence of climate change on agriculture productivity and food security in the context of Ethiopia. We use 2011–2020 state level data set of four major seasonal crops of Cash and Food in Ethiopia, namely, barley, wheat, maize, and sorghum. Methodologically, we apply the productivity function and the Ricardian approaches in the modelling for simulating the association of climate change with agriculture productivity. This study documents the interconnectedness among changes in climate, security of food and agriculture, indicating how the prior changes bring the latter kind of alterations. In general, agriculture in Ethiopia is prone to changes in climate and variations in the levels of precipitation, posing threats to food security of the rural population. The specific findings of this study highlight sorghum and barley as the majorly impacted stable crops through changes in meteorology. Furthermore, the study shows that barley production has vital contribution to causing insecurity of food in Ethiopia. The study ends with recommending some policy prescriptions and adaptation methods for mitigating the detrimental effects of climate change on production of agriculture and security of food in Ethiopia.